NILAI SERAPAN KARBON PADA POHON DI TAMAN MEDIAN JALAN KOTA PEKANBARU DAN PEMANFAATANNYA SEBAGAI MEDIA PEMBELAJARAN POSTER PENCEMARAN UDARA DI SMA - Nabila Yudia Tamara; Sri Wulandari; L.N. Firdaus L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Information on the value of carbon absorption in green open spaces whose carbon stock values are stored in biomass is needed to describe the condition of an ecosystem. This study aims to determine the value of carbon absorption of trees on the median parks in the city of Pekanbaru. Furthermore, the value of carbon is integrated with a learning media product in the form of a poster. This research was carried out on the median parks in Pekanbaru City in December 2020 - January 2021. The data was taken using a non-destructive method, namely using the roaming method by calculating the entire DBH and the height of all individual trees in the research location. Furthermore, the measurement data were analyzed allometrically and the tree height obtained was then processed using the allometric formula and converted as a carbon uptake value. The results showed that the total carbon absorption value in the median park of Pekanbaru are 2920.5 Ton ha-1. The results of the data have a relationship with learning materials such as in KD 3.11 and 4.11 class X Senior High School about environmental changes, especially on air pollution material, so that the results of the study can be used as a poster media design on air pollution material for class X Senior High School studentsKey Words: Carbon Absorption, Median Park, Poster